(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
Ernest Hemingway’s "A Farewell to Arms" explores the profound effects of war on human relationships, emotional resilience, and existential reflection. This article analyzes the novel’s key themes, including the futility of war, the fragility of love, and the quest for meaning in chaos. By examining Hemingway's minimalist prose and its influence on modern literature, this study highlights the novel’s enduring relevance as a critique of wartime humanity.